The performance of principals of primary schools in western Riyadh for administrative tasks in the light of knowledge management processes from their own point of view - Al Rafdh, Fatemah Mohammad (Journal of Educational and Psychological Sciences, 2023)
The study aimed to identify the reality of the primary school principals' performance of administrative tasks in the light of knowledge management processes. The researcher used the descriptive survey method, and the questionnaire as a tool consisting of (66) phrases divided into two axes that were distributed to a simple random sample of (156) principals in governmental and private schools for the primary stage, west of the city of Riyadh, and using the statistical program (SPSS). Elementary schools west of Riyadh practice planning in the light of knowledge management processes with an average of (4.29 out of 5), then organization with an average of (4.27), both with a (very high) degree, then school communication with an average of (4.19) and a (high) degree. Based on the results, the researcher recommended the need to create an environment An occasion to share knowledge among female employees and encourage them to do so, and invest various material and human resources in a way that helps achieve educational goals efficiently and effectively, and develop guides for school employees on how to apply knowledge management processes and guide them in what suits them, in addition to proposals for future studies on the subject.
Keywords: improving performance; school principals; west of Riyadh; in the light of knowledge management